Mentoring in Financial Report Preparation Based on SAK EMKM for Micro-Enterprises - Trinandari Prasetya Nugrahanti; Laela Lanjarsih; IGP Ratih Andaningsih (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This community service project was initiated in response to limited financial literacy and weak financial reporting practices among micro enterprises in Jatimurni Village, Bekasi Regency. Many entrepreneurs have not been able to prepare financial statements per the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM), thus hindering business growth and their access to financial institutions. This program aims to improve micro-entrepreneurs' ability to prepare standardized financial reports through a mentoring approach based on the Participatory Rural Appraisal (PRA) method. The activities include planning, training, mentoring, monitoring, and evaluation for three months, with data collection techniques in observations, interviews, and pre- and post-assessments. The results showed a significant increase in participants' understanding and skills in recording transactions, compiling ledgers, and compiling financial statements in accordance with SAK EMKM, supported by a strong positive correlation between participation intensity and learning outcomes (r = 0.78). Mentoring also encourages behavioral change towards financial discipline and accountability. In conclusion, the program effectively bridges the gap between theory and practice, empowering entrepreneurs to manage finances independently and sustainably. This initiative contributes to the national agenda of formalizing MSMEs and financial inclusion.